y = x² + 3
dy/dx = -2x
d²y/dx² = -2
2006-10-25 18:54:32
·
answer #1
·
answered by c00kies 5
·
0⤊
0⤋
dy/dx= d/dx (-x^2) + d/dx(3)
= (-2x) + 0 since 3 is a constant
=-2x
d^2y/dx^2=-2
2006-10-26 04:41:22
·
answer #2
·
answered by techy_crazy 2
·
0⤊
0⤋
The first derivative (dy/dx), is y=-2x.
The second derivative (d^2y/dx^2) is y=-2.
2006-10-26 01:53:54
·
answer #3
·
answered by Gimmip 2
·
0⤊
0⤋
this question is clear......
ther are many probabilities of assumption like
1. -(x^2+3) 2. (-x^2+3) first one
even after that
wather its x^(2+3) or x^2 + 3 means (x^2)+3
in general sence the problem you mentioned is considered as
-(x^2) +3
dy/dx= -2x
d^2x/dy^2 = -2
2006-10-26 02:04:15
·
answer #4
·
answered by jeevan k 1
·
0⤊
0⤋
dy/dx= -2*x
d^2y/dx^2= -2
That follows the following formula:
y=ax^b+c
dy/dx=(ba)x^(b-1)
2006-10-26 01:55:30
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
dy/dx = -2x
d^y/dx^2 = -2
2006-10-26 04:42:53
·
answer #6
·
answered by Hesam 1
·
0⤊
0⤋
dy/dx=-2x
d^2y/dx^2=-2
2006-10-26 03:16:59
·
answer #7
·
answered by bubbly 2
·
0⤊
0⤋